Instructional Leadership Behavior among Principals of Two Schools in Lalitpur, Nepal - Lamsal, Bishnu (Journal of Technical and Vocational Education and Training, 2022)
Instructional leadership is the position in any educational institute that can utilize individual skills and knowledge to ensure the academic performance of students with necessary support for all teachers, students, and school staff. There are various components and dimensions of instructional leadership, such as planning, curriculum design and development, training delivery and professional development, evaluation and monitoring of teachers, and assessment of students. The purpose of the study is to explore the perceptions of school principals about instructional leadership and narrate their experiences. The research adopted a qualitative research method in which principals of renowned schools of Lalitpur district of Nepal were interviewed as the participants. The study shows that principals of high-performing schools possess certain qualities as instructional leaders. Since the study was conducted with limited participants, it can be further taken to larger extent to explore additional details and dimension about instructional leadership.